Customers’ perceived value towards the service in Islamic banking: Confirmatory factor analysis - Suryani Suryani (Journal of Economics, Business, and Accountancy Ventura, 2015)
This study attempts to analyze the dimensionality of the concept of perceived value in Islamic banking sector, adapting to six dimensions of the GLOVAL scale and one additional dimension that is spiritual as measurement of perceived value to Islamic banking service sector. Design, methodology or approach is the total of 106 customers of financial entities surveyed, and confirmatory factor analysis was used to verify the reliability and validity of the scale of perceived value. It was found that perceived value is a multidimensional construct, composed of seven dimensions such as functional value of the establishment, functional value of the personnel, functional value of the service, functional value price, emotional value, social value, and spiritual value. The scale of overall perceived value in financial services was obtained, which was composed of seven dimensions and represented by 26 items that are significant for their measurement. It was also found that there are emotional and professionalism as dominant indicators in overall perceived value. It implies that a scale of measurement of the value is perceived by consumers in Islamic banking sector which incorporates valuations of customer value. The proposed model and study findings can greatly help researchers and practitioners understand the perceived value in Islamic Banking sector.